Slope of a polar curve

Calculus Level 4

If the slope of the polar curve r = 1 + sin ( θ ) r = 1 + \sin(\theta) at θ = π 4 \theta = \dfrac{\pi}{4} can be expressed as a b -\sqrt{a} - b for positive integers a a and b b , then find a + b a + b .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

{ x = r cos θ = cos θ + sin θ cos θ y = r sin θ = sin θ + sin 2 θ since r = 1 + sin θ \begin{cases} x = r\cos \theta = \cos \theta + \sin \theta \cos \theta \\ y = r\sin \theta = \sin \theta + \sin^2 \theta \end{cases} \quad \small \color{#3D99F6} \text{since }r = 1 + \sin \theta

{ d x d θ = sin θ + cos 2 θ d y d θ = cos θ + sin 2 θ \begin{cases} \dfrac {dx}{d \theta} = - \sin \theta + \cos 2 \theta \\ \dfrac {dy}{d \theta} = \cos \theta + \sin 2 \theta \end{cases}

d y d x = d y d θ d x d θ = cos θ + sin 2 θ sin θ + cos 2 θ d y d x θ = π 4 = cos π 4 + sin π 2 sin π 4 + cos π 2 = 1 2 + 1 1 2 + 0 = 1 2 \begin{aligned} \implies \dfrac {dy}{dx} & = \dfrac {\frac {dy}{d\theta}}{\frac {dx}{d\theta}} = \dfrac {\cos \theta + \sin 2 \theta}{- \sin \theta + \cos 2 \theta} \\ \dfrac {dy}{dx}\bigg|_{\theta = \frac \pi 4} & = \dfrac {\cos \frac \pi 4 + \sin \frac \pi 2}{- \sin \frac \pi 4 + \cos \frac \pi 2} = \frac {\frac 1{\sqrt 2}+1}{-\frac 1{\sqrt 2}+0} = - 1 - \sqrt 2 \end{aligned}

a + b = 2 + 1 = 3 \implies a+b = 2+1 = \boxed{3}

Exactly! Done this way!

Md Zuhair - 4 years, 2 months ago

In general, with r = f ( θ ) r = f(\theta) , we have that x = r cos ( θ ) x = r\cos(\theta) and y = r sin ( θ ) y = r\sin(\theta) and thus

d y d x = d y d θ d x d θ = d r d θ sin ( θ ) + r cos ( θ ) d r d θ cos ( θ ) r sin ( θ ) \dfrac{dy}{dx} = \dfrac{\dfrac{dy}{d\theta}}{\dfrac{dx}{d\theta}} = \dfrac{\dfrac{dr}{d\theta}\sin(\theta) + r\cos(\theta)}{\dfrac{dr}{d\theta}\cos(\theta) - r\sin(\theta)} .

Now in this case r = 1 + sin ( θ ) d r d θ = cos ( θ ) r = 1 + \sin(\theta) \Longrightarrow \dfrac{dr}{d\theta} = \cos(\theta) , and thus

d y d x = cos ( θ ) sin ( θ ) + ( 1 + sin ( θ ) ) cos ( θ ) cos 2 ( θ ) ( 1 + sin ( θ ) ) sin ( θ ) = 2 sin ( θ ) cos ( θ ) + cos ( θ ) ( cos 2 ( θ ) sin 2 ( θ ) ) sin ( θ ) = sin ( 2 θ ) + cos ( θ ) cos ( 2 θ ) sin ( θ ) \dfrac{dy}{dx} = \dfrac{\cos(\theta)\sin(\theta) + (1 + \sin(\theta))\cos(\theta)}{\cos^{2}(\theta) - (1 + \sin(\theta))\sin(\theta)} = \dfrac{2\sin(\theta)\cos(\theta) + \cos(\theta)}{(\cos^{2}(\theta) - \sin^{2}(\theta)) - \sin(\theta)} = \dfrac{\sin(2\theta) + \cos(\theta)}{\cos(2\theta) - \sin(\theta)} .

So the slope at θ = θ 4 \theta = \dfrac{\theta}{4} is d y d x = 1 + 2 2 0 2 2 = ( 2 + 2 ) 2 = 2 1 \dfrac{dy}{dx} = \dfrac{1 + \dfrac{\sqrt{2}}{2}}{0 -\dfrac{\sqrt{2}}{2}} = - \dfrac{(2 + \sqrt{2})}{\sqrt{2}} = -\sqrt{2} - 1 , and so a + b = 2 + 1 = 3 a + b = 2 + 1 = \boxed{3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...